2016
DOI: 10.1016/j.cbd.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential recruitment of co-regulatory proteins to the human estrogen receptor 1 in response to xenoestrogens

Abstract: The diverse biological effects of xenoestrogens may be explained by their ability to differentially recruit co-regulatory proteins to the estrogen receptor (ER). We employed high-throughput receptor affinity binding and co-regulatory protein recruitment screening assays based on fluorescence polarization and time resolved florescence resonance energy transfer (TR-FRET), respectively, to assess xenoestrogen-specific binding and co-regulatory protein recruitment to the ER. Then we used a functional proteomic ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Our study establishes a correlation between the fraction of cells actively transcribing TFF1 and GREB1, and the recruitment of ERα and FOXA1 at the gene loci. This result, in the context of studies which profiled the protein-protein interactions formed by ERα in the presence of E2 and BPA [20, 21], suggest that activation of GREB1 does not depend on the same cofactors as TFF1 . Supporting this speculation, different subsets of cofactors are necessary for maximal activation of E2 responsive genes [34].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our study establishes a correlation between the fraction of cells actively transcribing TFF1 and GREB1, and the recruitment of ERα and FOXA1 at the gene loci. This result, in the context of studies which profiled the protein-protein interactions formed by ERα in the presence of E2 and BPA [20, 21], suggest that activation of GREB1 does not depend on the same cofactors as TFF1 . Supporting this speculation, different subsets of cofactors are necessary for maximal activation of E2 responsive genes [34].…”
Section: Discussionmentioning
confidence: 80%
“…Notably, the efficiency of ERα interactions with several cofactors including MED1 and SRC-3 is altered when the receptor is bound by estrogen-mimicking chemicals known as endocrine-disrupting chemicals (EDCs) [20, 21]. Humans are continuously exposed to a complex mixture of EDCs including genistein (Gen) from soy products, Bisphenol S (BPS), and Bisphenol A (BPA) from plastics [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that treatment of human breast cancer cells with 17β-estradiol (E2) dramatically increases the accumulation of R-loops, particularly in regions of the genome containing estrogen-induced genes 35 . Interestingly, estrogen receptor α (ERα) specifically interacts with Thrap3 under conditions of E2 exposure 36 . Because E2-dependent R-loop generation and rearrangement in breast cancer cells are mainly enriched at E2-responsive genomic loci, it is possible that Thrap3 might be localized to E2-responsive genomic loci with ERα and that this localization is followed by DDX5 recruitment for precise removal of cotranscriptional R-loops in breast cancer cells, which is critical for cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the impact of adsorption of EE2 to SWCNTs on estrogen receptor (ER) binding by EE2, a fluorescence polarization (FP)-based ER binding assay was utilized. The advantages of this assay over traditional radioligand binding assays and detailed methods have been described previously . Briefly, the recombinant human estrogen receptor 1 ligand binding domain (ESR1-LBD) was produced in bacterial cells and purified for use in the assays.…”
Section: Experimental Sectionmentioning
confidence: 99%